Prenatal wellbeing of mothers, their partners, and couples: a cross-sectional descriptive study - Tia Mäkelä; Terhi Saisto; Katariina Salmela-Aro; Jenny Miettinen; Harri Sintonen; Hanna Rouhe (BMC, 2023)
Abstract Background Prenatal posttraumatic stress symptoms (PTSS), fear of childbirth (FOC), and depressive symptoms have been related to various negative effects during pregnancy, childbirth, and in the postnatal period. This study evaluates the prevalence of PTSS, FOC, depressive symptoms, and health-related quality of life (HRQoL) among pregnant women, their partners, and as couples. Methods In a cohort of 3853 volunteered, unselected women at the mean of 17th weeks of pregnancy with 3020 partners, PTSS was evaluated by Impact of Event Scale (IES), FOC by Wijma Delivery Expectancy Questionnaire (W-DEQ-A), depressive symptoms by Edinburgh Postnatal Depression Scale (EPDS), and HRQoL by 15D instrument. Results PTSS (IES score ≥ 33) was identified among 20.2% of the women, 13.4% of the partners, and 3.4% of the couples. Altogether, 5.9% of the women, but only 0.3% of the partners, and 0.04% of the couples experienced symptoms suggestive of phobic FOC (W-DEQ A ≥ 100). Respectively, 7.6% of the women, 1.8% of the partners, and 0.4% of the couples reported depressive symptoms (EPDS ≥ 13). Nulliparous women and partners without previous children experienced FOC more often than those with previous children, but there was no difference in PTSS, depressive symptoms, or HRQoL. Women's mean 15D score was lower than partners' and that of age- and gender-standardized general population, while partners' mean 15D score was higher than that of age- and gender-standardized general population. Women whose partners reported PTSS, phobic FOC, or depressive symptoms, often had the same symptoms (22.3%, 14.3%, and 20.4%, respectively). Conclusions PTSS were common in both women and partners, as well as in couples. FOC and depressive symptoms were common in women but uncommon in partners, thus they rarely occurred simultaneously in couples. However, special attention should be paid to a pregnant woman whose partner experiences any of these symptoms.